Novel chalcone derivatives and pharmaceutical compositions comprising the same - Lin, Chun-Nan; Wang, Jih-Pyang (2004)
Disclosed herein are novel chalcone derivatives of formulas (I), (II) and (III): 1 wherein each of the substituents is given the definition as set forth in the Specification and Claims. These compounds are demonstrated to have anti-inflammatory activities and thus can be used in the treatment of an inflammatory disorder in a subject.